Hopf Amplification Originated from the Force-Gating Channels of Auditory Hair Cells - 田霖 张艳平 龙长才 (Chinese physics letters, 2016)
The sense of mammalian hearing exhibits nonlinear phenomena which are most significant to hearing function, such as nonlinear dynamic compression, nonlinear tuning and combination tones. These nonlinear phenomena are suggested to originate from the Hopf amplification within the cochlea, while the mechanism underlying the Hopf amplification remains elusive. According to the experimental results of force-gating channel operation in hair cells, through a theoretic model, this work reveals a velocity-dependent open probability of force-gating channels in auditory hair cells, and a velocity-dependent active force produced by the force-gating channel operating, which makes sensors hear typical Hopf vibrators with nonlinear hearing phenomena.